Analysis and Research of the Planetary Ring Bevel Gear Power Split Type Continuously Variable Transmission - Gu Cunhang; Mao Huping; Wang Qiang; Shi Yuncai (Jixie chuandong)
Based on the traditional traction planetary ring cone friction continuously variable transmission,the planetary ring bevel gear power split type continuously variable transmission is firstly proposed,and the derivation with two methods of its overall gear ratio is carried out. Furthermore,the power flow direction and distribution relationship are obtained accurate judgments. Finally,the overall transmission efficiency of the transmission system is analyzed and calculated in detail,comparative analysis of the transmission efficiency with the original planetary rings cone continuously variable transmission is carried out by using the example. The numerical range of total input power is obtained with the power split ratio diagram. The results show that,the improved planetary ring bevel gear power split type continuously variable transmission not only has a higher transmission efficiency than the original planetary rings cone continuously variable transmission,but also the total input power of the improved transmission can be up to the original transmission a few times,a high-power transmission is achieved.